Intelligent Data Analysis An Introduction - Berthold, Michael R.; Hand, David J. (Springer Berlin Heidelberg, 2003)
This monograph is a detailed introductory presentation of the key classes of intelligent data analysis (IDA) methods. The 12 coherently written chapters by leading experts provide complete coverage of the core issues. The previous edition was completely revised and a new chapter on kernel methods and support vector machines and a chapter on visualization techniques were added. The revised chapters from the original edition cover classical statistics issues, ranging from the basic concepts of probability through general notions of inference to advanced multivariate and time-series methods, and provide a detailed discussion of the increasingly important Bayesian approaches. The remaining chapters then concentrate on the area of machine learning and artificial intelligence and provide introductions to the topics of rule induction methods, neural networks, fuzzy logic, and stochastic search methods. The book concludes with a higher-level overview of the IDA processes, illustrating the breadth of application of the presented ideas. The second edition features an extensive index, which makes this volume also useful as a quick reference on the key techniques in intelligent data analysis
Keywords: Pattern Recognition; Statistical Theory and Methods; Information Storage and Retrieval; Artificial Intelligence; Probability and Statistics in Computer Science; Data Mining and Knowledge Discovery; Pattern recognition; Statistics; Information storage and retrieval; Artificial intelligence; Mathematical statistics; Data mining; Datenanalyse